2023
DOI: 10.3389/fendo.2023.1148417
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific effects of oxidative balance score on the prevalence of diabetes in the US population from NHANES

Abstract: BackgroundThe relationship between oxidative balance score (OBS) and diabetes remains poorly understood and may be gender-specific. We conducted a cross-sectional study to investigate the complex association between OBS and diabetes among US adults.MethodsOverall, 5,233 participants were included in this cross-sectional study. The exposure variable was OBS, composed of scores for 20 dietary and lifestyle factors. Multivariable logistic regression, subgroup analysis, and restricted cubic spline (RCS) regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…This study found that higher OBS values were associated with a decreased risk of elevated FBG ( 24 ). Oxidative stress is involved in the onset and progression of diabetes and IR ( 14 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This study found that higher OBS values were associated with a decreased risk of elevated FBG ( 24 ). Oxidative stress is involved in the onset and progression of diabetes and IR ( 14 ).…”
Section: Discussionmentioning
confidence: 70%
“…Based on previous studies, lower scores across all OBSs indicate higher oxidative stress, which is associated with adverse clinical outcomes ( 21 ). The relationships between OBS and hypertension ( 23 ), diabetes ( 24 ), nonalcoholic fatty liver disease ( 25 ), cancer ( 26 ), all-cause mortality ( 27 ) and biological aging ( 28 ) have been intensively investigated and widely discussed. However, relatively few studies probe the correlation between attitudes toward OBS and MetS risk.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous research and experience, 23–25 the OBS calculation method combined 16 dietary components and 4 lifestyle components. The lifestyle components are physical activity, body mass index (BMI), alcohol consumption, and cotinine.…”
Section: Methodsmentioning
confidence: 99%
“…The Oxidative Balance Score (OBS) is a comprehensive metric assessing the balance between pro-oxidants and antioxidants in an individual's diet and lifestyle [ 7 , 14 ]. Generally, a higher OBS indicates a dominance of antioxidants over pro-oxidants.…”
Section: Introductionmentioning
confidence: 99%